The Association Between Relationship Events and Experiences and Partner Evaluations: An Ideal Standards Perspective - Chesterman, Susan; Karantzas, Gery C.; Marshall, Emma M. (Frontiers in Psychology, 2021)
Drawing on the Ideal Standards Model, the current study investigated whether the relationship events and experiences that occur on a given day in romantic relationships were associated with partner evaluations. Individuals in a current romantic relationship (N=104) completed daily measures of positive and negative relationship events and experiences and partner evaluations for seven consecutive days. As hypothesized, findings demonstrated that on a given day negative relationship events and experiences were associated with evaluating partners as falling short of mate ideals, while positive relationship events and experiences were associated with evaluating partners as more closely meeting ideals. The findings demonstrate the importance of the relational context in evaluations of a partner against ideal standards.